2021
DOI: 10.1101/2021.05.26.21257854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corowa-kun: Impact of a COVID-19 vaccine information chatbot on vaccine hesitancy, Japan 2021

Abstract: Background: Few studies have assessed how mobile messenger apps affect COVID-19 vaccine hesitancy. We created a COVID-19 vaccine information chatbot in a popular messenger app in Japan to answer commonly asked questions. Methods: LINE is the most popular messenger app in Japan. Corowa-kun, a free chatbot, was created in LINE on February 6, 2021. Corowa-kun provides instant, automated answers to frequently asked COVID-19 vaccine questions. In addition, a cross-sectional survey assessing COVID-19 vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The study was a web-based experiment on a French sample population, which found that interacting with a chatbot could promote more positive attitudes toward COVID-19 vaccines and intention to vaccinate [ 32 ]. A study (preprint) also showed an increase in vaccine acceptance in Japanese adults after using “Corowa-kun,” a chatbot in LINE instant messenger [ 33 ]. Direct comparison between our study with these studies were difficult because of differences in the study methods, sample characteristics, and outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The study was a web-based experiment on a French sample population, which found that interacting with a chatbot could promote more positive attitudes toward COVID-19 vaccines and intention to vaccinate [ 32 ]. A study (preprint) also showed an increase in vaccine acceptance in Japanese adults after using “Corowa-kun,” a chatbot in LINE instant messenger [ 33 ]. Direct comparison between our study with these studies were difficult because of differences in the study methods, sample characteristics, and outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Apps can be useful to affect COVID-19 vaccine hesitancy, escape, and other related problems. In [44], a national experience performed in Japan is reported. The authors assessed an application (App) based on mTech.…”
Section: Example Of Mtech Applicationsmentioning
confidence: 99%
“…In our study, it has been highlighted how mobile technology can be particularly helpful in this moment on this issue. It was highlighted how specific Apps can play an important role as a communication tool capable of allowing the dissemination of correct information, fighting the infodemic [44,45,47], and recalling citizens with calibrated messages [48].…”
Section: Highlightsmentioning
confidence: 99%